3,4,5-Trimethoxychalcones Tubulin Inhibitors with a Stable Colchicine Binding Site as Potential Anticancer Agents - Maadh Jumaah; Tutik Dwi Wahyuningsih; Melati Khairuddean (Universitas Gadjah Mada, 2022)
The development of microtubule perturbing drugs is one of the most promising anticancer therapeutic methods. Unfortunately, limitation such as drug resistance, adverse side effects, complex formulations and synthesis, and limited bioavailability of these microtubule perturbing drugs has aroused the search for a new molecule of the tubulin system. Different substituents of chalcone were designed, synthesized, and determined for inhibition of tubulin assembly and toxicity in human cancer cell lines based on conventional colchicine site ligands and a computer model of the colchicine binding site on tubulin. A molecular docking study indicated that the chalcone scaffold could fit the colchicine site on tubulin in a similar orientation to the natural product. The 3,4,5-trimethoxyphenyl ring, which occupies the same sub-cavity as the equivalent molecule in colchicine, appeared to benefit the ligand of α,β-tubulin interaction. Several 3,4,5-trimethoxychalcone compounds demonstrated improved cytotoxicity against MCF-7 cells and inhibited tubulin assembly in vitro as potently as colchicine. The most active chalcone 1 with the IC50 of 6.18 ± 0.69 μM prevented the proliferation of human cell lines at micromolar concentrations, causing microtubule destabilization and mitotic arrest in humans inhibiting breast cancer cells.